Why should I recycle?: a smart kid's guide to a green world - Kumar, Aanchal Broca (New Delhi The Energy and Resources Institute, 2014)
Do you know that the amount of waste generated everyday on Earth, in cities alone, is enough to fi ll a fl eet of trucks covering 5,000 kilometres? We have been creating and dumping waste into the environment for far too long. Well, all this waste is destroying the environment and the world we live in. The time has come when we must sit up and make amends. Small and consistent efforts will go a long way in dealing with this mounting issue. Why Should I Recycle? helps us understand the principle of Reduce, Reuse, and Recycle to ensure that we play our part in making the world a cleaner, healthier, and better place.
Keywords: Recycling (Waste, etc.)